Use of arbuscular mycorrhizal fungus Rhizoglomus irregulare and compost to improve growth and physiological responses of Phoenix dactylifera 'Boufgouss'. (27th May 2021) - Anli, Mohamed; Symanczik, Sarah; El Abbassi, Abdelilah; Ait-El-Mokhtar, Mohamed; Boutasknit, Abderrahim; Ben-Laouane, Raja; Toubali, Salma; Baslam, Marouane; Mäder, Paul; Hafidi, Mohamed; Meddich, Abdelilah
Abstract: Date palm ( Phoenix dactylifera L.) is an important crop in arid zones and plays significant ecological and socio-economic roles. During the last decades, date palm groves were subjected to degradation due to extensive soil exploitation and low soil fertility. The use of biological techniques is essential to improve date palm development. The present work aims at assessing the effect of two different doses of compost (5% and 20%) and inoculation with the arbuscular mycorrhizal fungus (AMF) Rhizoglomus irregulare on growth and development of date palm seedlings. The treatments comprised control and application of 5 and 20% of compost with R. irregulare individually or in combination. Growth, physiological, histological, and mycorrhization traits were assessed. Obtained results showed that compost applied at a low dose (5%) alone or in combination with the AMF stimulated root length, leaf area, root dry weight, nitrogen, phosphorus and potassium contents, stomatal conductance and chlorophyll fluorescence and increased the number of sclerenchyma fibers, the number of vascular bundles, root diameter, and lignification of the endodermis of date palm seedlings compared to control. Compost at low doses combined or not with AMF can successfully be applied as biofertilizers for improving the growth and development of date palm.